Constructing a versatile hybrid harvester for efficient power generation, detection and clean water collection. (April 2022) - Xu, Yunlong; Bai, Zhiqing; Xu, Guangbiao; Shen, Hua
Abstract: Exploring renewable green energy and clean water resources is a significant and long-term measure to guarantee the sustainable development of future society. At present, developing hybrid devices that can continually produce electricity and fresh water are particularly in demand. Herein, a fiber-shaped hybrid harvester composed of a water collect component with contrasting wettability surface and liquid-solid triboelectric component is proposed, which can efficiently extract fresh water from a moist environment and convert water drop energies into electrical power at the same time. By systematically manipulating the dopamine/lysine mass ratio, proportion of alternating superhydrophilic/hydrophobic surface, electrode length, and tribolayer thickness, the optimized integrated hybrid device provides the water collection efficiency of 3.2 g/h and generate the current of 41.5 nA and output power of 0.23 μW. Moreover, this device can maintain desirable durability and stability of water collection and power generation even after various deformation, soaking, and long-time exposure. Due to these advantages, the harvester can be used as the power supply for charging various capacitors and also as a self-powered sensor for intelligent environmental detection systems, such as monitoring fog intensity, the volume/frequency of raindrops, and the pipe water leakage. This work not only realizes the perfect combination of fresh water collection and electricity production but also provides novel insight to develop versatile hybrid harvester devices for obtaining multiple renewable resources. Graphical Abstract: ga1 Highlights: A versatile fiber-shaped hybrid energy harvester composed of water collector and liquid-solid TENG was proposed. The hybrid device integrates the functions of clean water collection, electricity generation, and self-powered sensor. The device can provide the water collection efficiency of 3.2 g/h and simultaneously generate output power of 0.23 μW. The device exhibits good durability and stability in both water collection and power generation even in harsh conditions.